Troubled Vision
IX, 243 p.
Keywords: Troubled Vision is an interdisciplinary collection of essays that explores the interface between gender, sexuality and vision in medieval culture. The volume represents an exciting array of scholarship dealing with visual and textual cultures from the Eleventh to the Fifteenth centuries. Bringing together a range of theoretical approaches that address the troubling effects of vision on medieval texts and images, the book mediates between medieval and modern constructions of gender and sexuality. Troubled Vision focuses thematically on four central themes: Desire, looking, representation and reading. Topics include the gender of the gaze, the visibility of queer desires, troubled representations of gender and sexuality, spectacle and reader response, and the visual troubling of modern critical categories.